VD_FINDINFO Décision / 2012 / 554 vom 9. Juli 2012 - VD Tribunal cantonal (2012)
CLASSEMENT DE LA PROCÉDURE, ADMISSION DE LA DEMANDE, CONCURRENCE DÉLOYALE | 326ter CP, 23 LCD, 3 LCD, 319 CPP (CH), 393 al. 1 let. a CPP (CH)